“Archimedes Point” and the Crisis of Western Political Modernity—On Hannah Arendt’s Criticism of Information Alienation - Jiaxing Li (Proceedings, 2022)
Hannah Arendt’s “Archimedes point” theory comes from her magnum opus “Human Condition” which described the character of modern society and criticized the phenomenon of information alienation in modern society. When people put themselves on the “Archimedes point”, the information obtained by observation and thinking is divorced from their living life and true conditions. This alienated way of generating and processing information is the reason for the crisis of western political modernity. Firstly, Arendt uses the concept of “Archimedes point” to explain the characteristics of the second stage of the phenomenon of “world alienation”, that is, people treat things around them in a state of alienation and indifference. Secondly, Arendt analyzes the influence of modern science of “Archimedes point” on the way people produce and process information, that is, when modern natural science processes information, it makes the information content singular and digitization and the understanding of information in all process-oriented ways, all the characteristics rooted in people’s minds made people deal with human affairs in the same way. Arendt further explains how the “Archimedes point” mode of generating and processing information threatens modern western politics, that is, this mode will lead to the assimilation of human beings, people will lose reflective ability and obey the “historical law” that humans create by themselves, then fall into the ideological control of totalitarian governments. Based on the study of all this, it can be seen that in the “Archimedes point” mode, the way modern natural science processes information, has led to a series of political crises that may escalate into totalitarian phenomena.